HISTORICAL AND AESTHETIC STUDY ON THE SIKAYU WOVEN FABRIC OF BOLAANG MONGONDOW - Exel Stevanel Pontolaeng; Meyer W. Matey; Ferdinand Pangkey (SoCul: International Journal of Research in Social Cultural Issues, 2023)
Sikayu woven fabric not only has historical value as a cultural expression, but is also recognized as a work of art that has aesthetic value, so the purpose of this study is to identify the history of Sikayu woven fabric and identify the aesthetic value of each supporting element of Sikayu woven fabric. This research adopts a qualitative method that produces descriptive data, utilizing observation, interviews with sources, and literature studies to obtain accurate information, this research was basically carried out in Mogolain Kotamobagu as a research location because it supports researchers in conducting data analysis. The results showed that Sikayu woven fabric is not only a textile product, but also a symbol of historical and cultural values. The visualization of these values is reflected in the form, motif, art structure, art style, and art function that form the elements of the work. The unity, complexity, and solemnity of each work are clear evidence of the rich artistic values contained in the Sikayu woven fabric. The implications of this research are the history and aesthetics of the Sikayu woven fabric.